Single phase short circuit calculation for 380 V overhead lines considering the elements used in neutral conductor earthing - Alaa aldin Housam aldin (Tishreen University, 2019)
When a single phase short circuit happens at the end of overhead lines 380/220 V, it is important to know the value of short current in the place where protection isin order to test its sensitivity. The short circuit current calculation is carried out without considering the resistance of earthing elements. The scientific references give the value of longitudinal impedance of the phase conductor loop and neutral conductor in overhead lines by ignoring the elements of neutral conductor earthing. In our research, we are trying to suggest a method considering earthing elements, when we calculate the single phase short circuit current at the end of overhead line loaded by concentrated load. The MATLAB has been used to get the results. The results showed the necessity of considering earthing units in calculating the single phase short circuit, and it is necessary to insert a correction factor in the mathematical equations which are used to calculate the single phase short circuit factor for overhead lines conductors which are used in low voltage networks.